2019
DOI: 10.3390/nu11091967
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Consumption of Oligosaccharides Greatly Increases L-Cell Density without Significant Consequence for Adult Eating Behavior

Abstract: Oligosaccharides (OS) are commonly added to infant formulas, however, their physiological impact, particularly on adult health programming, is poorly described. In adult animals, OS modify microbiota and stimulate colonic fermentation and enteroendocrine cell (EEC) activity. Since neonatal changes in microbiota and/or EEC density could be long-lasting and EEC-derived peptides do regulate short-term food intake, we hypothesized that neonatal OS consumption could modulate early EECs, with possible consequences f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 82 publications
1
10
0
Order By: Relevance
“…Based on the longitudinal follow-up we performed, using feces collected at PND60 and PND130 ( Supplementary Figures 4A–D ), the microbiotal differences between transferred and control animals were minimal as early as PND60. This fading overtime was already observed in our earlier studies using neonatal prebiotic supplementations to induce early microbiological changes (i.e., prior to full weaning) ( Morel et al, 2015 ; Le Drean et al, 2019 ). Our manipulations of the microbiota composition might in fact have been applied too early as they were stopped before weaning, a time when intestinal microbiota is described as unstable ( Schloss et al, 2012 ) as a result of the change in the nature of the food consumed (see Laforest-Lapointe and Arrieta, 2017 for a review).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Based on the longitudinal follow-up we performed, using feces collected at PND60 and PND130 ( Supplementary Figures 4A–D ), the microbiotal differences between transferred and control animals were minimal as early as PND60. This fading overtime was already observed in our earlier studies using neonatal prebiotic supplementations to induce early microbiological changes (i.e., prior to full weaning) ( Morel et al, 2015 ; Le Drean et al, 2019 ). Our manipulations of the microbiota composition might in fact have been applied too early as they were stopped before weaning, a time when intestinal microbiota is described as unstable ( Schloss et al, 2012 ) as a result of the change in the nature of the food consumed (see Laforest-Lapointe and Arrieta, 2017 for a review).…”
Section: Discussionsupporting
confidence: 71%
“…Between PND137 and PND155, eating behavior was analyzed in physiological cages (Phecomb cages, Bioseb, Vitrol, France), as previously described ( Coupe et al, 2011 ; Le Drean et al, 2019 ). Briefly, rats were allowed to adapt individually to physiological cage during 1 day before data recording.…”
Section: Methodsmentioning
confidence: 99%
“…Inulin influences directly on the gut, including prebiotic effects, improvement of bowel function and glycolipid metabolism in the host, secretion of satiety hormone and increased short fatty acids (SCFAs) production [5][6][7][8]. Although the exact mechanism has not been elucidated, the gut microbiota has been considered as a potential modulating factor [9].…”
Section: Introductionmentioning
confidence: 99%
“…Dietary supplementation of GOS has also been linked with improvements in the transition to a mature intestinal microbiota in broiler chickens [12,15] and in suckling piglets [16,17]. In a study conducted with suckling male rats, in addition to changes in the intestinal microbiota, Le Dréan et al [18] observed GOS and FOS supplementation impacted entero-endocrine cell maturation by bringing about transient increases in the density of GLP-1 cells and the production of the satiety-related peptides GLP-1 and PYY.…”
Section: Introductionmentioning
confidence: 99%